Fatalistic Beliefs and Completion of the HPV Vaccination Series Among a Sample of Young Appalachian Kentucky Women. Issue 2 (14th January 2015) - Vanderpool, Robin C.; Dressler, Emily Van Meter; Stradtman, Lindsay R.; Crosby, Richard A.
Abstract Purpose Uptake and completion of the 3‐dose human papillomavirus (HPV) vaccine is important for the primary prevention of cervical cancer. However, HPV vaccination rates among adolescent females and young women remain low in certain geographic areas of the United States, including Appalachia. Although greater fatalistic beliefs have been previously associated with lower rates of preventive cancer behaviors among adults, little research exists on the impact of fatalism on HPV vaccination behaviors, especially among younger individuals. Therefore, the purpose of this study was to examine the association between fatalistic beliefs and completion of the full HPV vaccine series among young women, ages 18‐26, in Appalachian Kentucky. Results Data from this study were from a baseline survey completed by 344 women randomized into a communication intervention trial focused on increasing adherence to the 3‐dose HPV vaccine series. Principal components analysis was used to construct 2 fatalism‐related subscales from 8 survey questions. Findings In a controlled analysis, 1 subscale—"lack of control over cancer"—was significantly associated with not completing the full HPV vaccine series. In a rural area that experiences higher rates of cervical cancer, poverty, limited access to health care, and negative cancer‐related attitudes and experiences, fatalism may be common, even among young people. Conclusion Future educational and interventional research addressing fatalistic beliefs in a culturally sensitive manner may be warranted to improve HPV vaccination behaviors and impact cancer disparities among Appalachian women.